PTH-168 Tamoxifen induced gastric atrophy is regulated by the nf-Κb subunit nfkb1. (22nd June 2015) - Williams, JM; Norman, R; Tang, JM; Duckworth, CA; Caamano, J; Pritchard, DM; Burkitt, MD
Abstract : Introduction: Chronic Helicobacter felis infection of C57BL/6 mice results in gastric corpus atrophy. We have previously demonstrated that the outcome of H. felis infection is altered by deletion of specific NF-κB subunits. Nfkb1 -/- mice developed more severe gastric atrophy than wild-type (WT) mice 6 weeks after H. felis infection, whereas, Nfkb2 -/- mice were protected. The oestrogen receptor antagonist tamoxifen (TAM) has recently been shown to cause acute, reversible gastric atrophy in mice. In wild-type mice, this is associated with an increase in proliferating epithelial cells. We therefore hypothesised that gastric atrophy and altered epithelial cell turnover induced by TAM may be regulated by signalling involving NF-κB subunits. Method: Groups of 5 adult female C57BL/6 (WT), Nfkb1 -/-, Nfkb2 -/- and c-Rel -/- mice were administered 150 mg/kg TAM by IP injection. Animals were culled 72 h later and the gastric corpus underwent quantitative histological assessment. Gastric atrophy was quantified using a validated visual analogue score. Cell positional scoring was used to quantify H + /K + ATPase expressing cells and Ki67 positive cells; gastric epithelial cells expressing cleaved-caspase 3 were quantified in 10 high-powered fields (hpf) per mouse. Results: Morphological scoring demonstrated that TAM induced gastric atrophy in WT mice (median composite atrophy score (MCAS) 2 vs 0 in untreated WT mice, p < 0.01). This was associated with an increase in gastric corpus gland length compared to untreated WT mice (30.8 ± 2.1 vs 23.8 ± 0.5 cells per hemigland (cph), p < 0.05), and a 1.8 fold increase in Ki67 staining (p < 0.01). No change in the frequency of H + /K + ATPase or active caspase 3 positive cells was however seen. Nfkb2 -/- and c -Rel -/- mice exhibited similar phenotypes to WT mice. TAM treated Nfkb1 -/- mice developed more severe gastric atrophy with marked antralisation of the corpus epithelium (MCAS 4 vs 1 in untreated Nfkb1 -/- mice, p < 0.05). Nfkb1 -/- mice also exhibited corpus gland elongation after TAM treatment (36.1 ± 0.9 vs 23.9 ± 1.2cph, p < 0.01). This was associated with a >2.5 fold reduction in the number of parietal cells compared with untreated Nfkb1 -/- mice (p < 0.01) and a >2.3 fold increase in proliferating cells (p < 0.0001). An increased number of active caspase 3 positive cells (median 15 vs 6 in WT, p < 0.01) was also observed in TAM treated Nfkb1 -/- mice. Conclusion: NFKB1 mediated signalling influences the severity of gastric mucosal atrophy and cell proliferation following TAM administration. This correlates closely with our previous observations following H. felis infection. As NFKB1 signalling plays a similar role in two models of gastric atrophy, this suggests that it may have a generic role in regulating the development of this pathology. Disclosure of interest: None Declared.